Sosialisasi dan Pendampingan Penggunaan Pembayaran Elektronik (QRIS) Bagi Pemilik Usaha di Grand Depok City - Dwi Rachmawati; Hadi Wijaya; Noviyanti Noviyanti; Udriyah Udriyah; Ali Ridho; Ceskasumadewi Baharuddin; Nora Listiana (Eastasouth Institute, 2026)
Digital transformation is encouraging businesses to adopt cashless payments, one of which is through the Quick Response Code Indonesian Standard (QRIS). However, many business owners still haven't optimally utilized electronic payments due to limited digital literacy. This Community Service activity aims to increase the understanding and readiness of business owners in Grand Depok City to use QRIS. The methods used include socialization and participatory mentoring through technical training, implementation, and monitoring and evaluation. The results of the activity show an increase in understanding, digital literacy, and positive attitudes among business owners towards cashless transactions, thereby supporting business efficiency and strengthening MSMEs.